Assessment of the Effects of Low-Level Laser Therapy on the Thyroid Vascularization of Patients with Autoimmune Hypothyroidism by Color Doppler Ultrasound. (17th December 2012) - Höfling, Danilo Bianchini; Chavantes, Maria Cristina; Juliano, Adriana G.; Cerri, Giovanni G.; Knobel, Meyer; Yoshimura, Elisabeth M.; Chammas, Maria Cristina
Abstract : Background . Chronic autoimmune thyroiditis (CAT) frequently alters thyroid vascularization, likely as a result of the autoimmune process. Objective . To evaluate the effects of low-level laser therapy (LLLT) on the thyroid vascularization of patients with hypothyroidism induced by CAT using color Doppler ultrasound parameters. Methods . In this randomized clinical trial, 43 patients who underwent levothyroxine replacement for CAT-induced hypothyroidism were randomly assigned to receive either 10 sessions of LLLT (L group, n = 23 ) or 10 sessions of a placebo treatment (P group, n = 20 ). Color Doppler ultrasounds were performed before and 30 days after interventions. To verify the vascularity of the thyroid parenchyma, power Doppler was performed. The systolic peak velocity (SPV) and resistance index (RI) in the superior (STA) and inferior thyroid arteries (ITAs) were measured by pulsed Doppler. Results . The frequency of normal vascularization of the thyroid lobes observed in the postintervention power Doppler examination was significantly higher in the L than in the P group (P = 0.023 ). The pulsed Doppler examination revealed an increase in the SPV of the ITA in the L group compared with the P group (P = 0.016 ). No significant differences in the SPV of the STA and in the RI were found between the groups. Conclusion . These results suggest that LLLT can ameliorate thyroid parenchyma vascularization and increase the SPV of the ITA of patients with hypothyroidism caused by CAT.